2018
DOI: 10.1186/s12913-018-3050-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV and early hospital readmission: evaluation of a tertiary medical facility in Lilongwe, Malawi

Abstract: BackgroundDelivery of quality healthcare in resource-limited settings is an important, understudied public health priority. Thirty-day (early) hospital readmission is often avoidable and an important indicator of healthcare quality.MethodsWe investigated the prevalence of all-cause early readmission and its associated factors using age and sex adjusted risk ratios (RR) and 95% confidence intervals (CI). A retrospective review of the medical ward database at Kamuzu Central Hospital in Lilongwe, Malawi was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…48 The 29 studies provided information about post-discharge outcomes for 92 781 patients. Most studies were from North America; [11][12][13][14]20,21,24,25,[29][30][31]33,34,40,44 nine studies were from Africa, including five from South Africa, 5,23,27,38,43 one from Malawi, 26 one from Mozambique, 36,37 one from Tanzania, 41 and one from Zambia; 32 two studies were from southeast Asia; 22,35 one study was from Latin America; 28 and two studies were from Europe (table ). 39,42 The study from Mozambique reported outcomes in children; 36,37 all other studies were done in adults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…48 The 29 studies provided information about post-discharge outcomes for 92 781 patients. Most studies were from North America; [11][12][13][14]20,21,24,25,[29][30][31]33,34,40,44 nine studies were from Africa, including five from South Africa, 5,23,27,38,43 one from Malawi, 26 one from Mozambique, 36,37 one from Tanzania, 41 and one from Zambia; 32 two studies were from southeast Asia; 22,35 one study was from Latin America; 28 and two studies were from Europe (table ). 39,42 The study from Mozambique reported outcomes in children; 36,37 all other studies were done in adults.…”
Section: Resultsmentioning
confidence: 99%
“…11 studies reported the proportion of patients with advanced HIV disease (CD4 count <200 cells per µL), 5,[11][12][13]28,29,32,[35][36][37]41 which ranged from 16% to 91%. 11 studies reported length of hospital stay, 5,[11][12][13]23,26,28,29,32,43,44 which ranged from 4 days to 12 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent hospitalization may suggest clinical failure in this subgroup of non-suppressed women. Hospital readmissions are frequent among HIV positive adults when compared to their HIV negative counterparts [25]. Persistent viremia above 200 copies/ml has been found to predispose one to higher morbidity, virologic failure and mortality especially among cases of delayed ART switch to 2nd line therapy [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…These are described elsewhere and have provided useful information about targeted prevention measures. [42][43][44] Through meetings with key personnel responsible for these databases, we learnt their implementation logistics and ongoing processes. We assessed data collection forms, which influenced the production of our database forms.…”
Section: Bmj Global Healthmentioning
confidence: 99%